On Circular Migration: Conceptual approaches, Theoretical dimensions and Policy programmes - López-Sala, Ana; Godenau, Dirk (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Circular migration is an attractive term that has entered the academic and policy debate during the last decade in North America and Europe. The popularity of the concept is partly linked to the search of new formulas to manage international migration. In spite of this popularity circularity remains a vague and elusive concept, and definitions have ranged from simple descriptive to prescriptive ones. Based on a conceptual and theoretical review this article highlights the analytic and empirical distinction between spontaneous and induced circularity. Induced circularity can be understood as a distinctive pattern of mobility resulting from the implementation of new temporary and seasonal labour mobility schemes.